ANALISIS FAKTOR YANG MEMPENGARUHI PROFITABILITAS (ROA) BANK SYARIAH DI INDONESIA TAHUN 2014-2018 - Rizky Ramadhanty; Aris Soelistyo (Program Studi Ekonomi Pembangunan, 2020)
Syariah banks is that implement syariah principle in Indonesian. Has introduced banking instutions using syaria system can be a alternative choice for muslim communities in Indonesian. In Indonesia, syariah banks have begun to develop since the issue of law No. 7 year 1992 on banking. As institutions that are important role banks need to pay attention to their performance to operate properly. Performance levels can be assessed using one of the profitability indicators that is Return On Asset (ROA). ROA is a description of the bank’s productivity in managing its funds to get the overall profit. There are indicators related to ROA analysis such as FRD, CAR, BOPO. The purpose of this research is to know the influence of FDR, CAR, BOPO on the profitability of ROA on syariah banks in Indonesian. The method used is multiple regression. Data is processed through e-views. The number of samples used is 13 syariah banks. The result showed the fDR signicantly negative effect on ROA with a coefficient value of -3.77E and a probability of 0.019, CAR has a significant positive effect on ROA with a coefficient value of 0.205 and a value of probability 0.0004, BOPO has a significant negative effect with a coefficient negative effect with a coefficient value of -0.106 and a probability of 0.000. FDR, CAR, BOPO is a simultan effect on ROA.